Kebutuhan Air untuk Tanaman Terung ( Solanum melongena. L) pada Lempung Liat Berpasir di Tanah Ultisols - Ratna Shanti (Agrifarm : Jurnal Ilmu Pertanian, 2019)
The purpose of this study was to  determine  optimum water requirement of eggplant (Solanummelongena  L) onsandy clay loam soil of Ultisols during  it growth period. The experiment was conducted on 5th May to 27thAgust2017  in glass house Faculty of Agiculture, Mulawarman University, Samarinda. The pot experiment was designed Completely Randomized Design  that consisted of four treatments  level with seven replications. Treatment  based  on  water avaibility (WA), those are  :  A = 494 ml  (50 % WA),   B = 670 ml  (75 % of  WA) C = 846 ml ( 100 %  of WA)  and  D =   1022 ml (  125 % of WA).Each  experiment  pot contained   10 kg  dried  soil.  The  treated  pots(after watering)   have  weight  respectively,   A=  10494  g,  B =  10670  g,  C= 10846 g, and   D= 11022 g. These  pots will be  weighted  every  daycontinouslyduring plant  growth and  maintained   those pot  weight  respectively.Vegetative  and  generative data  were collected  and  statistical analyzed using variance analysis. If the treatments showed significant different  effect, the statistical analysis of those treatment continued by Least Significant Different (LSD) test at 5% level to find out the  optimum water requirement level. The results of the experiment showed that  treatments of watering  was significant   effect on the average of vegetative  parameters, (vegetative  growth i.e.plant height at the age 20, 40, and 60 days,  blooming after planting.) and  significant  effect for generative parameters (fruit number, length and  fruit weight).The optimum  water requirement   for  eggplant at  506 ml pot-1  therefore during growth period  eggplant   needs   40,731 ml of waterfor  maximum yield.